BIOMONITORING OF AIR QUALITY IN ISTANBUL METROPOLITAN TERRITORY WITH EPIPHYTIC LICHEN PHYSCIA ADSCENDENS (FR.) H. OLIVIER - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2017)
Trace elements in the air are toxic to humans and the ecosystem. This study was designed to monitor atmospheric element deposition in the European side of the Istanbul metropolis was monitored using epiphytic foliose lichen species, Physcia adscendens (Fr.) H. Olivier, sampled from 12 sites. The lichen samples were categorized according to thallus-size, and analysed for Aluminium (Al), Arsenic (As), Cadmium (Cd), Chromium (Cr), Iron (Fe), Manganese (Mn), Nickel (Ni), Lead (Pb), Vanadium (V) and Zinc (Zn) contents. The spatial distributions of elements in the city of Istanbul were shown in digital pollution maps. Results indicated that average values of all element accumulations of the collected lichens were more from that of the reference values. The lichen samples representing air elemental concentrations in declining order of mean values are as follows: Cd > Cr > Fe > Ni > V > Pb > Al > As > Zn > Mn. The highest heavy metal concentration values were measured in urbanized sites close to the heavy traffic activity. Cd, Ni and Pb elements showed a statistically significant correlation with distance to the main road and industrial sampling sites rather than lichen's age or size. This study strengthens the use of lichens as a biomonitor of airborne pollutants.
Keywords: Biomonitoring; heavy metal; air pollution; lichen; Physcia adscendens; Istanbul; TRACE-ELEMENT CONCENTRATIONS; SOLID-WASTE INCINERATOR; HEAVY-METAL POLLUTION; TURKEY; MOSSES; REGION; FURFURACEA; POLLUTANTS; INDICATORS; DEPOSITION